TEKNO EKONOMI PROSES DAUR ULANG ANODA GRAFIT BATERAI LITHIUM-ION KENDARAAN LISTRIK - Miswanto, Agus; Wahyudi, Tatang; Prakosa, Agus; Birawidha, David Candra (Indonesian Mining Journal, 2023)
Graphite is the primary material for battery anodes used in electronic devices such as cell phones, laptops, and electric vehicles. Exploiting natural graphite in Indonesia is still in the exploration stage. The ever increasing demand for energy storage devices poses challenges in producing battery-grade graphite. One possible approach is to recycle the graphite anode (AG) from used Lithium-ion Batteries (LIB) into battery components. By utilizing waste as a raw material, production costs are lower as well as the use of LIB becomes more sustainable. This study discusses the techno-economics of AG recycling from electric vehicle (EV) LIBs. Secondary data is used from various research reports, journals, and books published through the official website as references and assumptions in calculations and analysis. Mechanical separation to remove plastic components, washing with organic solvents (using dimethyl carbonate-DMC) and using dimethyl carbonate (DMC) and N-methyl-2-pyrrolidone (NMP), then washing process with H2SO4 + H2O2 purifies graphite to be reused as anode material for the new LIB. Economic analysis shows that the Net Present Value is IDR 388,675,699, the Internal Rate of Return is 33.79% per year, and the Payback Period is two years and ten months. These three indicators show that the project is financially viable. The sensitivity analysis shows that it is still profitable if there is an increase in production costs of up to 20% and a decrease in selling prices of up to 20% or USD 12,000 per tonne.